SORPTION ROPERTIES OF LATVIAN CLAYS AND ENVIRONMENTAL PROTECTION SURVEY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The survey has been comprised in historical sequence. It has been attempted to group literature sources in a way that we consider to be the most relevant in the publication. Analysis of literature led to the following conclusions: during the last years most important and most advanced ways in investigations of Latvian clay surface characteristics have been found: Value determination of clay specific surface; Clay’s porous structure investigation; Cation exchange capacity determination; Characteristics of organoclays; Catalytic characteristics of Latvian clays; Practical usage of clays in waste water treatment; Usage of clays in adulterants elimination from vegetable oils; Clays as catalysts in of organic compound reactions; New type of sorbent from rapeseed oil treatment waste. Experimental measurements supplement data base about surface characteristics of Latvian clay samples.